The Responsibility of Social Welfare Institutions in the Implementation of Collecting Money or Goods in the Digital Era - Cahyady, Yadhy; Isretno Israhadi, Evita (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
ABSTRACT The implementation of the collection of money or goods is carried out by the community through legal entity social organizations, consisting of associations or foundations. The organization of the collection of money or goods must be obtained a permit from the minister who organizes government affairs in the social sector, governor, or regent/mayor in accordance with their authorities, with the requirements, including that they must attach a registration document of a social welfare institution. In this digital era, the implementation of money or goods collection is mostly performed through digital applications, electronic money services, and social media. In order to organize the collection of money or goods, the licensed organizer is obliged to provide a report along with the progress report. Furthermore, the monitoring process is carried out by the government's internal supervisory officers, the curbing task force, and the community. The normative juridical method is used in this research, with a statutory approach based on secondary data obtained through document studies. Then, it would be analyzed using deductive logic. The legal issues in this research are: First, how is the responsibility of social welfare institutions in organizing the collection of money or goods in the digital era. Second, why is it necessary to supervise the implementation of money or goods collection carried out by social welfare institutions in the digital era. From this research, the writer expects to obtain a formulation of norms that can provide legal knowledge about the responsibility of social welfare institutions in organizing the collection of money or goods in the digital era.